Parametric investigation of CO2-MIPs production using suspension polymerisation method - Ali Nabavi; Eseosa M. Eguagie; Beichen Li; Stella Georgiadou; Goran Vladisavljevic; Sai Gu (2015)
Parametric investigation of CO2-MIPs production using suspension polymerisation method